Application of data deduplication systems - Лященко, Андрій Олександрович (Technology audit and production reserves, 2013)
The subject of the article is data deduplication. The theme of the article is the application of the existing technologies of the data deduplication in practice. The purpose of the study is to demonstrate the ability to deploy the content management system using the existing technologies of deduplication. When writing the article the component-oriented methodology of research was used. The result of the research is the development of the final directions to deploy and install the Web-systems of content management using the technologies of data deduplication. The directions presented in the article can be used as guidances to deploy and install the web-systems of content management using the technologies of data deduplication. Conclusions. The article describes the methods of deduplication and the existing systems of data deduplication. The article also provides directions to install the content management systems using the technologies of data deduplication